Sustainable development and energy security level after Ignalina NPP shutdown - Augutis, Juozas; Krikštolaitis, Ričardas; Pečiulytė, Sigita; Konstantinavičiūtė, Inga (Technological and Economic Development of Economy, 2011)
The paper presents the investigation of the impact of Ignalina Nuclear Power Plant (NPP) shutdown on Lithuanian energy security. The system of energy security indicators, covering technical, economic and socio-political aspects is presented. The integral characteristic of these indicators shows the level of energy security. The paper analyses the Lithuanian energy security level in 2007. To make a comparison, the energy security level in 2010, after the shutdown of Ignalina NPP, when Lithuanian Power Plant in Elektrėnai becomes the main electricity producer, is forecasted. Two alternatives are analysed: Lithuanian Power Plant uses either gas or heavy fuel oil for electricity production. The security level of each indicator, each indicator block and the total security level are presented as the result. Energy security indicators, which increased or decreased after the shutdown of Ignalina NPP, are analysed, including the indicators which have had the greatest impact on the change in energy security level. The influence of Ignalina NPP shutdown on CO2 emissions is presented. Also, electricity generating costs for different types of electricity production at a different discount rate are presented.